Judicial Review of Child Violence Committed by Caregivers - Dwi Aniffatul Azizah; Ina Monica Putri (Jurnal Hukum dan HAM Wara Sains, 2024)
This study examines the legal protection of children from violence in Indonesia, focusing on the implementation of Law Number 35 of 2014 concerning Child Protection. The research methodology employed is a normative juridical approach with analysis of primary and secondary data. Primary data includes the law itself, its implementing regulations, and court decisions related to child abuse cases. Secondary data comprises legal articles, academic journals, and reports from the Indonesian Commission on Child Protection (KPAI). The findings indicate that Law Number 35 of 2014 provides a comprehensive legal framework for protecting children from various forms of violence. However, its implementation faces challenges in terms of consistent law enforcement, access to adequate social and mental health services, and the need for increased public awareness. Case studies such as that of Janna Amira Priyanka underscore the urgency of improving child protection from violence. Recommendations from this research include enhancing the capacity of law enforcement agencies, expanding social service networks, educating and raising awareness among the public about children's rights, and improving inter-agency coordination to effectively enhance child protection in Indonesia.